Taxation of trust income - Mnyatheli, Ntobeko (Department of Commercial Law, 2026)
The content of this paper is based on a prescribed syllabi for the fulfilment of a Master of Law degree. The paper seeks to provide a detailed research on the principles applicable in the taxation of trust income on the present day South African Tax Law and to analyse and criticize them. Emphasis will be on the relevant sections of the Income Tax Act and Case law.